A randomised trial of home energy efficiency improvement in the homes of elderly COPD patients. - Osman, L; Ayres, J; Garden, C; Reglitz, K; Lyon, J; Douglas, J (2010)
A randomised trial of 178 patients in Aberdeen, UK with a previous hospital admission for chronic obstructive pulmonary disease (COPD) was carried out in order to determine whether improving home energy efficiency improves health-related quality of life in COPD patients. 118 patients were randomised and 60 agreed to monitoring only. Energy efficiency upgrading was carried out in 42% of homes randomised to intervention. Independent energy efficiency action was taken by 15% of control participants and 18% in the monitoring group. The main outcome measures were respiratory and general health status, home energy efficiency and hospital admissions. Intention-to-treat analysis found no difference in outcomes between the two groups. In 45 patients, who had energy efficiency action independent of original randomisation, there were significant improvements in respiratory symptom scores (adjusted mean 9.0, 95% CI 2.5-15.5), decreases in estimated annual fuel costs (- pound65.3, 95% CI - pound31.9- - pound98.7) and improved home energy efficiency rating (1.1, 95% CI 0-1.4). COPD patients are unlikely to take up home energy efficiency upgrading, if offered. Secondary "pragmatic" analysis suggests that those who do take action may achieve clinically significant improvement in respiratory health, which is not associated with an increase in indoor warmth.